The feasibility and efficacy of ultrasound-guided percutaneous laser ablation for multifocal papillary thyroid microcarcinoma - Zhang, Lu; Zhang, Gui Ping; Zhan, Wei Wei; Zhou, Wei (Frontiers in Endocrinology, 2022)
Objective: To evaluate the feasibility and efficacy of percutaneous laser ablation (PLA) for patients with multifocal papillary thyroid microcarcinoma (PTMC). Materials and methods: A cohort of patients who underwent ultrasound (US)-guided PLA for primary PTMC were enrolled in this study. The patients were divided into multifocal PTMC(multi-PTMC) group and unifocal PTMC (uni-PTMC) group. Before PLA, conventional US and contrast-enhanced ultrasound (CEUS) were performed to evaluate the PTMC and cervical lymph nodes. The operation time, energy, power, amount of isolation liquid, and complications during PLA were recorded. Patients were followed up at 2 days, 1, 3, 6, months and every 6 months after that. Volume reduction rate (VRR), local tumor recurrence, and lymph node metastasis after PLA were observed. Results: The study included 12 patients with 26 PTMCs and 60 patients with 60 PTMCs. The operation time, total energy, and amount of isolation liquid in multi-PTMC group were more than those in uni-PTMC group (P = 0.000, 0.007, and 0.020, respectively). The mean follow-up durations in multi-PTMC and uni-PTMC groups were 19.75±11.46 months (6-36 months) and 16.33±10.01 months (4-40 months), with the similar VRR of the ablated lesions in two groups. One and three cases with newly developed PTMCs were observed in multi-PTMC group and uni-PTMC group during follow-up, respectively. There was no regrowth of treated lesions, lymph node metastasis, or distant metastasis. At the end of the follow-up, all the ablated lesions in two groups completely disappeared or only remained scar strips. Conclusion: PLA is a safe and effective technique for treating multifocal PTMC, which might be an alternative technique for patients who are not eligible or are unwilling to undergo surgery.